Designing appropriate extension delivery systems for promoting indigenous livestock breeds - Kanna K Siripurapu; Sajal Kulkarni; Sabyasachi Das (Journal of Livestock Biodiversity, 2025)
Indigenous livestock breeds represent the collective heritage of the communities they are associated with, and cannot be conserved separately from their production systems. Such breeds will survive only when indigenous knowledge systems in which they have been embedded also survives. Modern livestock breeding and development programmes, however, heavily rely on only a handful of livestock breeds and genes, with narrow range of quantitative traits such as – quick growth and weight gain. Further, such development programmes and associated extension and delivery systems seldom acknowledge the role of indigenous socio-cultural, traditional economic and indigenous knowledge systems in improvement and conservation of indigenous livestock breeds and germ plasm. A study was conducted in eleven districts of Maharashtra to examine the relationship and embeddedness of a specific indigenous livestock breed within the socio-cultural landscape of its custodian indigenous community. Results of the study suggest that Indigenous livestock management systems are highly evolved and well positioned for improvement and sustainable management of both the indigenous livestock and associated genetic resources. However, indigenous knowledge on animal breeding is often “tacit” and not necessarily an expressed knowledge. Unlike modern science, the indigenous livestock management systems rely mostly on qualitative traits. Acknowledgement of their role and a little encouragement through designing inclusive institutions, extension services and delivery mechanisms could take improvement and conservation of indigenous livestock breeds/populations a long way.